SYNERGETICS POTENTIAL OF SOLID FORM OF VERSE (RONDO, RONDELE, TRIOLET) - Anatoliy Vyacheslavovich Ostankovich; Evgenia Viktorovna Shpak (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the most presentable in the history of Russian poetry solid form оf verse – a rondo, a rondele and a triolet. The unity of the research is provided with the methodological approach, which is based on understanding of fixed poetic forms as harmonious systems.